2019
DOI: 10.1101/761684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory non-coding small RNAs are diverse and abundant in an extremophilic microbial community

Abstract: 1Regulatory small RNAs (sRNAs) represent a major class of regulatory molecules that 2 play large-scale and essential roles in many cellular processes across all domains of 3 life. Microbial sRNAs have been primarily investigated in a few model organisms and 4 little is known about the dynamics of sRNA synthesis in natural environments, and the 5 roles of these short transcripts at the community level. Analyzing the metatranscriptome 6 of a model extremophilic community inhabiting halite nodules (salt rocks) fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…To address the paucity of knowledge on the transcriptional activities of halophilic microbial communities, we interrogated the metatranscriptome of the well‐characterized halophilic community inhabiting salt nodules in the Atacama Desert (Robinson et al ., 2015; Crits‐Christoph et al ., 2016; Finstad et al ., 2017; Gelsinger et al ., 2019; Uritskiy et al ., 2019). We sampled nodules from representative light and dark time‐points during the diel cycle, placing our transcriptional observations in the context of the metagenomic composition of the respective samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the paucity of knowledge on the transcriptional activities of halophilic microbial communities, we interrogated the metatranscriptome of the well‐characterized halophilic community inhabiting salt nodules in the Atacama Desert (Robinson et al ., 2015; Crits‐Christoph et al ., 2016; Finstad et al ., 2017; Gelsinger et al ., 2019; Uritskiy et al ., 2019). We sampled nodules from representative light and dark time‐points during the diel cycle, placing our transcriptional observations in the context of the metagenomic composition of the respective samples.…”
Section: Introductionmentioning
confidence: 99%
“…It is also likely that the large relative humidity and temperature changes in the Atacama Desert, throughout the diurnal (day/night) cycle, have a significant impact on microbiome functioning. In that regard, a recent study showed that halite communities have the capability for transcriptional regulation via small non‐coding RNAs (Gelsinger et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%